MODEL PEMBERDAYAAN PEREMPUAN MELALUI PENDIDIKAN KETERAMPILAN KEWIRAUSAHAAN DENGAN BIMBINGAN DALAM PENGEMBANGAN KERAJINAN TANGAN PAYETTE PADA MAJELIS TA'LIM PEREMPUAN PARUNG-BOGOR - Lily Rochaya (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2011)
This research is aimed to study a model of entrepreneurial skill learning at non formal educational institutions preparing women to become independent entrepreneurs. This study was conducted in the form of research and development (R &D) model employing mixed method (survey, evaluation and experiment). Its samples which were selected purposively covered four Islamic Women Groups in Bogor district. The model developed deals with the area of non formal education and is designed by the following steps : (1) developing concepts, (2) identifying target groups, (3) carrying out a need analysis, (4) determining objectives, (5) developing plans, (6) developing a curriculum and materials, (7) implementing the learning process, and (8) administering an evaluation.The result of the research shows that : (1) the model of interpreneurial skill learning using teaching methode with guidance is better than the one without guidance, (2) the result of the model interpreneurial skill learning using teaching methode with guidance is higher compared with the one without guidance. The model of women empowerment through interpreneurial skill learning with guidance in development of payette handycraft is effective in nurturing the intrepreneurial attitude and motivation by generating need for achivement motivation as well as managerial skills through practice and simulation.